Eosinophilia in autoimmune hepatitis: is there an association? - Mustafa, Ahmad Suhaimi; Tee, Hoi Poh; Che Aun, Azlida; Jaafar, Khairul Azhar; Satwi, Sapari (Malaysian Medical Associations, 2011)
Background: There were several reports on eosinophilic drug-induced hepatitis. We report a case of autoimmune hepatitis (AIH) presenting with eosinophilia in whom steroid therapy induces resolution of both eosnophilia and hepatitis. CASE REPORT: A 57 years old lady who presented with jaundice and right hypochondriac pain associated with tender hepatomegaly and urticarial rash. Blood investigations showed high eosinophil counts persistently ranging from 800 to 1500/mm3 with highly elevated bilirubin of 380 umol/L, alanine transaminase 750 U/L and aspartate transaminase of 1015 U/L. She has raised serum immunoglobulin IgG of 21.6 g/L. Liver biopsy showed moderate interface hepatitis and plasma cells infiltration suggesting AIH. However, her antinuclear antibody was negative. She had negative serology for hepatitis A, B and C and a normal ultrasound abdomen. Definite diagnosis of AIH was made based on Codified Dignostic Criteria of the International Autoimmune Hepatitis Group with aggregate score 17. On starting steroid, she had a complete normalization of liver function and eosinophil production induced by compounds released by basophills and mast cells, including eosinophill chemotactic facotr of anaphylaxis, leukotriene B4, complement complex (C5-C6-C7), interleukin 5, and histamine. AIH is characterized by an inflammation of the portal tract with lymphocytes and plasma cells, hypergammaglobulinemia and presence of a variety of circulatin autoantibodies. While eosionophilia is humoral (antibody-mediated), AIH is characterized by an inflammation of the portal tract with lymphocytes and plasma cells, hypergammaglobulinemia and presence of a varety iof circulatin autoantibodies. While eosionophillia is humoral (antibody-mediated), AIH is thought to be cell-mediated. Presence of both conditions in an individual is uncommon. In this case effort had been maed to rule out other cases of eosinophilia such as drug-induced or helminthic infections but there were all negative. The mechanism of dual-pathology in this case remains unresolved. CONCLUSION: Eosinophilia is not a diagnostic feature for AIH.An association wtih AIH is suggested in this case.